Pattern of Substance Use and Suicide Probability in Poly-Drug Users - Amany A Baalash; Ibrahim H Othman; Mohammed A Osman (Ridwan Institute, 2023)
Objective: The aim of this study is to examine the prevalence of suicidal thoughts and suicidal probability among sample of patients with poly-substance use disorder, and to examine the relation between pattern of drug use and suicidal thoughts. Study design: cross sectional case control study. Place and duration of study: Inpatient words of psychiatric and surgery departments of Tanta General, and University hospitals, Egypt, from May 2015 to June 2019. Methodology: Participants were 220 subjects, aged 18-45 years. We reviewed 110 individuals who fulfilled the DSM-5 criteria of substance use disorder for three or more substances, and their data were compared with that collected from 110 control persons. Results: Suicidal cases are highly present among patients with poly-substance use disorder 25.45%. Most of suicidal cases started using illicit substances under effect of peer pressure. Tramadol and cannabis dominated the list of used substances (94.55%), (62.73%) respectively. A statistically significant association with suicidality was found with longer duration of substance use (p<0.001), using cannabis (p=0.014), alcohol (p<0.001) and volatile (p=0.02), using substances while alone (p<0.05), and positive history of accidental overdose (p<0.05). Suicidal cases showed significant higher scores (P <0.0001) of suicide probability scale and subscales. Conclusion: This study demonstrated that abusing certain substances for long duration while being alone, in addition to history of overdose may trigger suicidal thoughts in patients with poly-substance use disorder, and that suicide probability is common consequences of poly-substance abuse.